Inhibition of Candida albicans cell growth and biofilm formation by a bioactive extract produced by soil Streptomyces strain GCAL-25 - Córdova-Dávalos, Laura E.; Escobedo-Chávez, Karla G.; Evangelista-Martínez, Zahaed (Archives of Biological Sciences, 2018)
Resistance to antifungal agents is a major public health concern since multidrug resistant (MDR) strains of Candida albicans have caused severe infections among immunosuppressed, diabetic and other hospital patients. This study focused on evaluating the effects of a bioactive extract (BEx) produced by a novel Streptomyces species on C. albicans cell germination and biofilm formation. Agar disk diffusion assays were used to select a streptomycete with inhibitory activity over C. albicans cells. Thereafter, minimal inhibition concentration (MIC) and time-kill values were obtained for the BEx prepared from the isolate GCAL-25. Also, the effects of BEx on biofilm formation were analyzed. Results showed that the GCAL-25 isolate from the Streptomyces genus displayed inhibitory activity on C. albicans. A paper disk soaked with BEx showed an inhibitory halo around confluent growing cells of C. albicans. The calculated MIC values for BEx indicated that C. albicans was three times more susceptible to BEx than the control fungicide, amphotericin B (AmpB). Time-kill studies with ½x and 1xMIC of BEx showed severe negative effects on cell viability, suggesting a strong fungicidal activity. In addition, an important reduction of C. albicans biofilm formation was observed. The BEx from Streptomyces sp. GCAL-25 altered yeast-to-hyphae transitions and induced abnormal cell morphology (e.g. cell shrinkage), including impairments of cell membrane integrity with negative effects on biofilm formation. https://doi.org/10.2298/ABS170908057C Received: September 8, 2017; Revised: November 29, 2017; Accepted: December 7, 2017; Published online: December 29, 2017 How to cite this article: Córdova-Dávalos LE, Escobedo-Chávez KG, Evangelista-Martínez Z. Inhibition of Candida albicans cell growth and biofilm formation by a bioactive extract produced by soil Streptomyces strain GCAL-25. Arch Biol Sci. 2018;70(2):387-96.